Intraoperative Burden of Flexible Intramedullary Nailing and Spica Casting for Femur Fractures in Young Children. Issue 7 (August 2021) - Barnett, Scott A.; Song, Bryant M.; Yan, Justin; Leonardi, Claudia; Gonzales, Joseph A.; Heffernan, Michael J.
Abstract : Background: Spica casting (Spica) remains the widely accepted treatment of closed femoral shaft fractures in young children aged 6 months to 5 years. In some centers, there has been a recent trend towards surgical fixation of these fractures with flexible intramedullary nails (FINs). Despite numerous studies evaluating both Spica and FIN treatment of femoral shaft fractures, there remains a paucity of data regarding patient burden during the intraoperative period. The purpose of this study was to compare the intraoperative burden, defined as anesthetic exposure, fluoroscopic duration, and radiation load, between Spica and FIN treatment of femoral shaft fractures in young children. Methods: A retrospective chart review was conducted for pediatric femoral shaft fractures presenting to a tertiary pediatric referral hospital from 2012 to 2017. Comparison groups included pediatric femur fractures treated with Spica and those treated with FIN. Outcomes included anesthetic exposure, fluoroscopy duration, and radiation exposure. In addition, length of stay, clinic visits, and complications were recorded. Results: Of 449 consecutive pediatric femur fractures treated at our center, 143 patients ages 2 to 6 years (mean age 3.8±1.4 y) met inclusion criteria. The Spica group contained 91 patients; FIN contained 52 patients. Mean anesthetic exposure was less for Spica compared with FIN [45.1 min, 95% confidence interval (CI): 38.0-52.3 vs. 90.7 min, 95% CI: 80.5-100.8 min; P <0.001]. On average, Spica procedures required less fluoroscopy time compared with FIN (15.4 s, 95% CI: 4.8-26.0 vs. 131.6 s, 95% CI: 117.6-145.6 s; P <0.001). Mean radiation load was less for Spica compared with FIN (1.6 mGy, 95% CI: 0.6-2.6 vs. 6.9 mGy, 95% CI: 5.7-8.1 mGy; P <0.001). There was no difference in length of hospital stay ( P =0.831), follow-up visits ( P =0.248), or complication rate ( P =0.645) between Spica and FIN groups. The most common complication was skin irritation for Spica (18.7%) and symptomatic hardware for FIN (17.3%). Conclusions: The findings of this study suggest that pediatric patients with femoral shaft fractures experience an increased intraoperative burden when treated with FIN compared with Spica. Treatment with FIN was associated with increased exposure to anesthesia, fluoroscopic duration, and radiation load despite similar complication rates when compared with Spica. Level of Evidence: Level III.